The Study of Electroluminescence and Reliability of Polyimide Films in High DC Fields - Jiaqi LIN; Ying LIU; Zhibin XIE; Xiaxia HE (Medžiagotyra, 2015)
Electroluminescence (EL) intensity of the polyimide (PI) films was tested under dc high electric field by home-made experimental device. The results showed that the EL intensity of PI films increased along with the electric field. EL intensity is approximately to background intensity when the electric-field intensity was less than 2.00 MV/cm. EL intensity increases along with increasing the electric field when electric-field intensity greater than 2.00 MV/cm. When electric-field at 2.80 MV/cm, EL intensity increasing strongly suggests that the excitation process related to hot electrons accelerated by the field approaching a critical threshold. Meanwhile, this work elaborates a method to deal with identical samples get different experimental data by using Weibull distribution method, and the concept of the reliability was presented. The nine groups of EL experimental data were analyzed, and the result showed that the lifetime of mid-value (t = 164.9 min). Mid-value of the breakdown field is E = 2.76 MV/cm. DOI: http://dx.doi.org/10.5755/j01.ms.21.4.9694